2016
DOI: 10.1093/bja/aew178
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of the acute respiratory distress syndrome on outcome after oesophagectomy

Abstract: Early and late ARDS after oesophagectomy increases intensive care and hospital length of stay. Given the high incidence of ARDS, cohorts of patients undergoing oesophagectomy may be useful as models for studies investigating ARDS prevention and treatment. Further investigations aimed at reducing perioperative ARDS are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
15
2
Order By: Relevance
“…Oesophagectomy patients were recruited into this trial as they represent a single cause with a reproducible and timed lung injury response that, historically, has been associated with increases in transpulmonary thermodilution-measured postoperative PVPI and EVLWI, inflammation and a high-rate of PPCs, including ARDS. 5 , 21 However, in contrast to previous trials in this population, 3 , 22 minimal postoperative increases in PVPI and EVLWI were observed in the placebo-treated patients, suggesting less lung injury and alveolar capillary leak in patients recruited to this trial.…”
Section: Discussioncontrasting
confidence: 66%
“…Oesophagectomy patients were recruited into this trial as they represent a single cause with a reproducible and timed lung injury response that, historically, has been associated with increases in transpulmonary thermodilution-measured postoperative PVPI and EVLWI, inflammation and a high-rate of PPCs, including ARDS. 5 , 21 However, in contrast to previous trials in this population, 3 , 22 minimal postoperative increases in PVPI and EVLWI were observed in the placebo-treated patients, suggesting less lung injury and alveolar capillary leak in patients recruited to this trial.…”
Section: Discussioncontrasting
confidence: 66%
“…Respiratory complications, mainly pneumonia, are a severe problem after esophageal surgery and at least in part responsible for the frequent need for postoperative critical care as well as for the high morbidity and mortality [2,[4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][20]. A better understanding of the presumably multifactorial pathogenesis of postoperative pulmonary impairment [15] is mandatory for the development of new preventive and therapeutic strategies that are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, abdomino-thoracic esophagectomies are high-risk surgical procedures, facing high rates of postoperative morbidity and mortality, even in high-volume surgical centers [2][3][4][5][6][7][8][9][10]. Apart from anastomotic complications, high rates of postoperative respiratory complications, especially pneumonia, are reported after abdomino-thoracic esophagectomy that cause a high postoperative morbidity, a frequent need for critical care, and poor postoperative short-term as well as unsatisfactory long-term oncological outcomes [2,[4][5][6][7][8][9][11][12][13][14][15]. Multiple factors were proposed to contribute to the pathogenesis of postoperative pulmonary complications like perioperative atelectasis after single-lung ventilation, post-thoracotomy pain affecting respiratory physiology, as well as intraoperative injury to the thoracic cavity and the lung [10,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…8 Even in the VINDALOO cohort, the ARDS incidence remains higher than that defined by the Lung Injury Prediction Score 27 28 and the postoperative complication incidence is very high, with the advantages of an initial insult of surgery at a specific time and a defined postoperative care pathway, 3 which facilitates the conduct of efficacy trials. We believe this work demonstrates that oesophagectomy continues to be a useful model for trialling translational therapeutic and preventative strategies for critical illnesses prior to engaging in larger, more complex and expensive trials.…”
Section: Methodsmentioning
confidence: 99%
“…2 We have previously shown that ARDS following oesophagectomy is associated with more non-respiratory organ failure, longer critical care and hospital stays, 3 and other groups have demonstrated worse shortterm and long-term outcomes associated with ARDS 2 and other pulmonary complications. 4 Severe infection and cardiac dysrhythmias are common.…”
Section: Introductionmentioning
confidence: 99%